Septic arthritis of the acromioclavicular joint secondary to methicillin-resistant Staphylococcus aureus infection. Issue 6 (21st June 2021) - Cooper, Blair; Obi, Nnamdi Jonathan Chukwura; Cheng, Kenneth
Abstract : Septic arthritis of the acromioclavicular joint (ACJ) is a rare pathology with very few documented case reports available in the literature. In addition, ACJ septic arthritis secondary to methicillin-resistant Staphylococcus aureus (MRSA) is a rarer pathology with only two previously documented case reports in the medical literature to our knowledge. We present the case of a 46-year-old man who was diagnosed with a confirmed ACJ septic arthritis secondary to MRSA following admission to the local trauma and orthopaedic service at a district general hospital. We aim to give an insight into this pathology and highlight the importance of the relationship between orthopaedics and microbiology in optimising patient care, particularly in a period of rising rates of antimicrobial resistance.